Isobutanol Synthesis from Syngas over Zn‐Cr Catalyst: Effect of Zn/Cr Element Ratio. Issue 9 (30th July 2018) - Tian, Shaopeng; Wu, Yingquan; Li, Kexuan; Xie, Hongjuan; Ren, Huaping; Zhao, Yuzhen; Miao, Zongcheng; Tan, Yisheng
Abstract: This report demonstrated the effect of Zn/Cr element ratio on Zn−Cr catalyst for isobutanol formation from the reaction of carbon monoxide hydrogenation. The catalysts of different Zn/Cr element ratios including 1 : 3, 1 : 1, 3 : 1 and 5 : 1 have been prepared by a facile coprecipitation approach and their activity evaluation of isobutanol formation by carbon monoxide hydrogenation were tested. The Zn1 Cr1 catalyst of Zn/Cr element ratio being 1 : 1 presented outstanding activity for iso‐butanol formation from the carbon monoxide hydrogenation, carbon monoxide conversion and isobutanol selectivity reached to the maximum to ∼32 % and ∼24 %, respectively. Multi‐Characterization including TEM, XRD, BET, XAS, H2 ‐TPR, CO2 ‐TPD and XPS were proceed to investigate the physico‐chemical property of catalysts. The characterization results display that the Zn1 Cr1 catalyst presents more nonstoichiometric Zn−Cr spinel and oxygen vacancies as well as more defects. The Zn1Cr1 catalyst also presents better properties of basicity, reducibility and BET surface area which are some other factors for better result of activity evaluation for isobutanol formation by carbon monoxide hydrogenation. Abstract : The Zn1 Cr1 catalyst presents more nonstoichiometric Zn−Cr spinel and oxygen vacancies as well as more defects. The Zn1 Cr1 catalyst also presents better properties of basicity, reducibility and BET surface area which are some other factors for better result of activity evaluation for isobutanol formation by carbon monoxide hydrogenation.Text for Table of Contents